Characteristics of survivors of juvenile sex trafficking: Implications for treatment and intervention initiatives. (September 2016) - Hargreaves-Cormany, Holly A.; Patterson, Terri D.
Abstract: The Behavioral Analysis Unit (BAU) III of the FBI conducted a study that expands upon a typology of offenders engaging in the sex trafficking of juveniles (STJ) (Hargreaves-Cormany, Patterson and Muirhead, 2016 ) by developing a STJ Survivor Spectrum of Characteristics. All 179 STJ survivors were included in the latent class analyses (LCAs). Further, a binary logistic regression (BLR) analysis was conducted to examine potential for increase in substance use. Data utilized for the study was derived from protocols developed to obtain demographic information on the offenders and survivors and various aspects of the nature of the criminal act(s) perpetrated by the offender. The second author's expertise and practical knowledge from the field regarding STJ offenders and survivors as well as their interviews were utilized to substantiate the empirical findings. The STJ survivors' age, known increases in substance use, motivation to cooperate/testify and family structure were used as indicators within the LCAs. Three latent classes emerged comprised of different STJ survivor age groups. Results suggested that differences between classes are likely attributed to developmental considerations/maturation. The BLR suggested that age of the STJ survivor was predictive of increase in alcohol use. Qualitative analysis of interviews provided in depth data and a lens into the perspectives of STJ survivors. Results enhance understanding of STJ survivors and inform treatment/intervention initiatives which may result in prevention/reduction of harm to juveniles.